A New Sphingosine Derivative from a Soft Coral of Nephthea Species of the Andaman and Nicobar Coasts - Bheemasankara Rao, Ch.; Chandra Sekhar, V.; Venkata Rao, D.; Sarvani, B.; Lakshmi, D.K.M. (Asian Journal of Chemistry, 2010)
A new sphingosine derivative, 2-N-nonanoyl-4,5-dihydrosphingosine (1) was isolated from a soft coral of Nephthea species of the Indian Ocean. Structure elucidation of the compound is based on interpretation of the spectral data.